What should every doctor know about ocular melanoma? - review of literature - Grzegorczyk, Aleksandra; Pachla, Magdalena; Mazur, Ewa (Journal of Education, Health and Sport, 2025)
The following paper aims to discuss melanoma located in the eye. Melanoma is a malignant tumor arising from melanocytes, in which a mutation has occurred in the DNA and pathological cells have developed. In most cases, this tumor is located on the skin exposed to sunlight, but it is also rarely located in the structures of the eye, especially in the part called uvea. It consists of the anterior and posterior parts, and in each of them the process of carcinogenesis can occur. The disease can cause very non-specific symptoms, mainly pain, visual disturbances, floaters and photopsia, or exophthalmos, but almost half of the cases are asymptomatic. Treatment is complicated and depends on many factors, radiation therapy, laser therapy, local resection and enucleation are used. Most patients are diagnosed when the changes are already extensive, or metastases occur. In the case of liver metastases, the prognosis is unfavorable. For this reason, we want every doctor to pay attention to the eye symptoms reported by the patient in order to be able to recognize this disease as soon as possible and treat it effectively.